Novel and simple electrochemical sensing platform based on polypyrrole nanotubes/ZIF-67 nanocomposite/screen printed graphite electrode for sensitive determination of metronidazole - Somayeh Tajik; Hadi Beitollahi; Fariba Garkani Nejad (Electrochemistry Communications)
Here, a simple, fast, and sensitive voltammetric sensor based on screen printed graphite electrode (SPGE) modified with polypyrrole nanotubes/zeolitic imidazolate framework-67 (PPy NTs/ZIF-67) nanocomposite is introduced for the metronidazole (MNZ) determination. The PPy NTs/ZIF-67 nanocomposite was synthesized and characterized by using X-ray diffraction (XRD) spectroscopy, field emission scanning electron microscopy (FE-SEM), and energy-dispersive X-ray spectroscopy (EDS) techniques. The developed sensor based on PPy NTs-ZIF-67 nanocomposite modified SPGE shows an obvious reduction peak at −650 mV for MNZ, mainly due to the synergistic effects of the ZIF-67 and PPy NTs. Differential pulse voltammetry (DPV) was found to be the most suitable method for MNZ detection, showing a linear dynamic range of 0.01–500.0 µM and a low limit of detection (LOD) of 0.004 µM. In investigating the practicability, the PPy NTs/ZIF-67/SPGE sensor demonstrated efficient practicability with satisfactory recoveries (97.1 % to 103.5 %) and low relative standard deviation (RSD) values of 1.8–3.6 % for MNZ determination in MNZ tablets and urine samples.